SOSIALISASI DAGUSIBU UNTUK MENINGKATKAN KESADARAN MASYARAKAT DI POSYANDU KEMUNING VIII, KECAMATAN KRIAN - Seran, Ivan Charles; Wahyuningsih, Arista; Rahmawati, Dewi; Ambari, Yani; Aristia, Bela Fevi; Amarullah, Adinugraha; Seran, Agustinus Alfred; Putra Tawakal, Muhamad Aulia; Ardian, Yohanes; Battista Leki, Karol Giovani (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2024)
DAGUSIBU (Get, Use, Store, and Dispose) is a drug counselling programme designed to increase community knowledge and awareness about the correct use of drugs, especially how to get, use, store, and dispose of drugs. This programme was implemented at Posyandu Kemunin VIII with the aim of increasing family awareness of medicine. The material provided is in the form of a general understanding of drugs and their classification which includes over-the-counter drugs, limited over-the-counter drugs, hard drugs, and hard drugs as well as pharmaceutical needs. We will then explain what drugs require precautionary measures if misused, and how to use and store them properly. The objective of the DAGUSIBU socialisation is to improve the community's knowledge and understanding of medicines. Activities are conducted through interaction, lectures and interactive discussions. The response and enthusiasm of the community in attending the activities, asking questions and actively participating in discussions regarding the purchase, use, storage and disposal of medicines. The good and correct use of medicines is evidence of this socialisation effort.